Fabrication of solid‐state nanopores and its perspectives. Issue 19 (8th September 2015) - Kudr, Jiri; Skalickova, Sylvie; Nejdl, Lukas; Moulick, Amitava; Ruttkay–Nedecky, Branislav; Adam, Vojtech; Kizek, Rene
<x xml:space="preserve">Abstract</x> Nanofluidics is becoming an extensively developing technique in the field of bioanalytical chemistry. Nanoscale hole embed in an insulating membrane is employed in a vast variety of sensing platforms and applications. Although, biological nanopores have several attractive characteristics, in this paper, we focused on the solid‐state nanopores due to their advantages as high stability, possibility of diameter control, and ease of surface functionalizing. A detection method, based on the translocation of analyzed molecules through nanochannels under applied voltage bias and resistive pulse sensing, is well established. Nevertheless, it seems that the new detection methods like measuring of transverse electron tunneling using nanogap electrodes or optical detection can offer significant additional advantages. The aim of this review is not to cite all related articles, but highlight the steps, which in our opinion, meant important progresses in solid‐state nanopore analysis.